Penerapan Metode CRM Pada Perancangan Sistem Informasi Penjualan Pakaian dan Aksesoris - Muhamad Firhan Al Farisi; Agung Purwanto (JURIKOM (Jurnal Riset Komputer), 2022)
VJ Collection is one of the stores engaged in trading that has sold various clothing and accessories products specifically for men, originating from various well-known brands. Sales are still made manually, and there is a risk of errors when calculating the total amount of the purchase price. To overcome this problem, a sales promotion information system will be proposed that can facilitate customers in getting to know the products on offer and make online purchase transactions. . The use of the CRM method is to record customers, give product ratings, and E-mail marketing. This research aims to design a website that suits the needs of VJ Collection and customers in carrying out the necessary transactions. The conclusions that can be obtained in this study are the system is considered to be able to assist the store in managing all transaction data and can view and create the desired report instantly. As for the application of CRM to the system, it is assessed that it can increase customer loyalty by using E-mail marketing which offers in the form of discount bonuses.